‘She was just like a Lassie’ - Maycock, Matthew (The British journal of criminology, 2022)
The subject of transgender rights has recently come under increasing scrutiny in many parts of the world. Despite this, there has been no research that analyses this issue from the perspective of cis-women living alongside transwomen in prison settings. This paper addresses this omission by analysing the views of fifteen cis-women in prison in Scotland, living on halls of four prisons that also housed transgender women. Findings are analysed across a range of areas incorporating the acceptance, support and solidarity as well rejection, feelings of vulnerability relating to transgender people in custody. Responses analysed highlight a diversity of views, reflective of wider societal perspectives about transgender people. This paper has relevance for prisons systems housing transgender people, and provides unique insights into the complexity of performances of gender within the contemporary prison settings.